The microwave bacteriome: biodiversity of domestic and laboratory microwave ovens - Iglesias, Alba; Martínez, Lorena; Torrent, Daniel; Porcar, Manuel (Frontiers in Microbiology, 2024)
Microwaves have become an essential part of the modern kitchen, but their potential as a reservoir for bacterial colonization and the microbial composition within them remain largely unexplored. In this study, we investigated the bacterial communities in microwave ovens and compared the microbial composition of domestic microwaves, microwaves used in shared large spaces, and laboratory microwaves, using next-generation sequencing and culturing techniques. The microwave oven bacterial population was dominated by Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes, similar to the bacterial composition of human skin. Comparison with other environments revealed that the bacterial composition of domestic microwaves was similar to that of kitchen surfaces, whereas laboratory microwaves had a higher abundance of taxa known for their ability to withstand microwave radiation, high temperatures and desiccation. These results suggest that different selective pressures, such as human contact, nutrient availability and radiation levels, may explain the differences observed between domestic and laboratory microwaves. Overall, this study provides valuable insights into 2 microwave ovens bacterial communities and their potential biotechnological applications.